Hubungan antara Kecerdasan Emosional dan Manajemen Konflik pada Pengurus BEM FKIP Universitas Lambung Mangkurat - Meiylina Ariani Ariani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study was motivated by the frequent conflicts that arise within student organizations due to differences in personality, background, and communication styles among members. The study aims to examine the relationship between emotional intelligence and conflict management among the executive board members of the Student Executive Board of the Faculty of Teacher Training and Education at Lambung Mangkurat University (BEM FKIP ULM). The study employed a quantitative approach using a correlational method. The research participants consisted of 68 BEM FKIP ULM executives selected using a saturation sampling technique. The research instruments comprised an emotional intelligence questionnaire and a conflict management questionnaire developed based on the theories of Goleman and Rahim. Data analysis was conducted using Pearson’s Product-Moment correlation with the assistance of SPSS. The results indicated a positive and significant relationship between emotional intelligence and conflict management, with a correlation coefficient of 0.733 and a significance level of 0.000. These findings suggest that the higher the emotional intelligence of the executives, the better their ability to manage conflicts constructively. This study concludes that emotional intelligence plays a crucial role in supporting the effectiveness of conflict management within student organizations.